Motive and rightness - Sverdlik, Steven, 1950- (Oxford : Oxford University Press, 2011)
This books answers the question: Does the motive of an action ever make a difference to whether that action is morally right or wrong? Sverdlik's answer is yes. He analyses the nature of motives and their relation to normative judgements and intentions, and argues that consequentialism gives the best account of these matters.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Consequentialism (Ethics)